ANALISIS PENGARUH LIKUIDITAS, DEBT TO EQUITY RATIO, FIRM SIZE, DAN ROA TERHADAP RETURN SAHAM (STUDI PADA PERUSAHAAN YANG TERDAFTAR PADA INDEKS SRI-KEHATI PERIODE 2012-2018) - Rahardian, Tito; Hersugondo, Hersugondo (Faculty of Economics and Business Diponegoro University, 2021)
This study aims to analyze the effect of liquidity, debt to equity ratio, and firm size on stock return. Current ratio used as a proxy from liquidity and ROA were used as proxy from profitability. The population that was used in this research consisted of all listed firms in Indonesia Stock Exchange 2020. After passed the purposive sampling method there were 16 firms obtained as samples from SRIKehati index during 2012-2018. The data analysis technique is path analysis, the wide version from multiple linear regression. The result of this research showed that current ratio and firm size have negatively non significant impact on stock returns, debt to equity ratio and ROA have positively significant impact on stock returns.